Forests and Rainfall - a Short Review - Dabral, B. G. (Indian Forester, 1983)
The subject of the elfect of forests upon rainfall has been of a controversial nature for a long time. In this paper, an effort has been made to review the various views expressed on the subject, so far. It appears that forests do not exert any significant influence upon the rainfall of a region.